Infiltration hazards for building siting studies. Issue 1 (29th January 2015) - Marx, Jeffrey D.; Ishii, Benjamin R.
Abstract : Facility siting studies have been a requirement for many years, specifically for facilities that must comply with OSHA's PSM program. Facility siting is frequently interpreted as performing a building siting study which adheres to the guidance given in API RP 752. Many of the siting studies conducted for large facilities over the past few decades have focused on explosion overpressure impacts to occupied buildings, with more simplistic evaluations for fire and toxic gas impacts. Toxic gas impact analyses often only evaluate the potential exposure of a building location, to a specific gas concentration, and do not evaluate the level of infiltration into the building where occupants may be impacted. Infiltration of flammable gases has largely been ignored in most building siting studies. Despite this oversight, this hazard is one which should be addressed when following the guidance found within API RP 752. Through the use of dispersion modeling and infiltration analyses, the hazards associated with flammable or toxic gas infiltration can be incorporated into a building siting study. This article outlines the process of conducting a building siting study in accordance with API RP 752, with specific emphasis on the consequence analysis for infiltration analyses. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 61–67, 2016